2016
DOI: 10.4269/ajtmh.15-0568
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Survival of Mycobacterium ulcerans in Watery Soil, a Potential Source of Buruli Ulcer

Abstract: Abstract. The reservoir of Mycobacterium ulcerans causing Buruli ulcer (BU) remains unknown. Here, sterilized watery soil was mixed with 2 × 10 6 colony-forming units (CFU)/g of M. ulcerans Agy99 or M. ulcerans ATCC 33728 and incubated in a microaerophilic atmosphere in the presence of negative controls. Both M. ulcerans strains survived in soil for 4 months with a final inoculum of 300-440 CFU/g. Further, three groups of five mice with and without footpad scarification were exposed to control soil or M. ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
2
10
0
Order By: Relevance
“…Accordingly, genomic analysis has suggested that M. ulcerans may reside inside one or several hosts (14), in agreement with previous observations (22). However, it was demonstrated in an experimental study that it can live as a free-living organism in its environmental niches, where it can survive for a long time despite its fragility under certain climatic conditions, such as solar light, temperature elevation, and UV light (14,29,37). As discussed above, these aspects have been poorly investigated, as the vast majority of field studies have relied upon molecular biology methods, which gave no clues regarding the viability of the detected mycobacteria.…”
Section: Ulcerans In the Environmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly, genomic analysis has suggested that M. ulcerans may reside inside one or several hosts (14), in agreement with previous observations (22). However, it was demonstrated in an experimental study that it can live as a free-living organism in its environmental niches, where it can survive for a long time despite its fragility under certain climatic conditions, such as solar light, temperature elevation, and UV light (14,29,37). As discussed above, these aspects have been poorly investigated, as the vast majority of field studies have relied upon molecular biology methods, which gave no clues regarding the viability of the detected mycobacteria.…”
Section: Ulcerans In the Environmentsupporting
confidence: 81%
“…In West Africa and Central Africa, outbreaks of Buruli ulcer in the 1980s were linked to man-made changes in the natural environment (34,35). More-recent studies have shown that in aquatic and swampy environments, M. ulcerans is detected in biofilms, soil, and aquatic insects (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural activities, such as farming particularly in swampy areas, puts cases in constant contact with moist/watery soil. Tian and others recently showed that MU strains can survive in soil for 4 months suggesting that BU could be acquired through contact of open wounds with watery soil as a transient source of infection 37. Moreover, Aboagye and others recently isolated MU from soil in a BU-endemic community along the Densu river basin of Ghana 38.…”
Section: Discussionmentioning
confidence: 99%
“…Another debatable topic in BU is disease transmission. Although not the main focus of this chapter, some epidemiological records and experimental laboratory results point to environmental exposure as the main source for BU acquisition, namely through contact of injured skin with water bodies and through insect bites [25,26,113,[129][130][131][132][133]. However, some work in Africa, Asia and Australia additionally raised the possibility of host genetics playing a major part in BU development [92,[134][135][136][137].…”
Section: Epidemiological Clues and The Search For Novel Resistance Anmentioning
confidence: 99%